2020
DOI: 10.3390/rel11040165
|View full text |Cite
|
Sign up to set email alerts
|

Religious Identity and Public Pro-Environmental Behavior in China: The Mediating Role of Environmental Risk Perception

Abstract: Although the positive relationship between religion and environmental behavior has aroused heated debate, empirical research on the relationship between religion and public pro-environmental behavior is still relatively insufficient. This paper aims to explore the group differences in the influence of religious identity on public pro-environmental behavior and the mediating role of environmental risk perception in religious identity and public pro-environmental behavior. Using the Chinese General Social Survey… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Risk perception of individual attitudes is a mediator between Religion and pro-environmental behavior [25]. The risks borne by individuals due to their behavior have opened awareness of the importance of protecting the environment by increased knowledge both about environmental conditions, environmental impacts, and environmental management practices have increased pro-environmental behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Risk perception of individual attitudes is a mediator between Religion and pro-environmental behavior [25]. The risks borne by individuals due to their behavior have opened awareness of the importance of protecting the environment by increased knowledge both about environmental conditions, environmental impacts, and environmental management practices have increased pro-environmental behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar fashion, where respondents who disagreed with “… supernatural influence over all environmental crises including flooding, volcanoes, and particularly the COVID-19 pandemic outbreak” significantly ( p value = 0.000) exhibited less likelihood of willingness to engage in global environmental conservation efforts, it goes further to substantiate the fact that, if properly harnessed, spirituality can be leveraged upon in environmental conservation efforts (Copeland, 2018 ). Although Jenkins and Chapple ( 2011 ) have observed that the few empirical studies on the relationship between religious beliefs and environmental engagement yielded mixed results, there is no denying the fact that even in more atheist China; Zeng et al ( 2020 ) have shown that study participants “with a religious identity are more willing to engage in public pro-environmental behavior than those without a religious identity.”…”
Section: Discussionmentioning
confidence: 99%
“… 24 Moreover, they found that individuals with religious identities are more willing to engage in public environmental protection behaviors than political participants without religious identities. 25 …”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…24 Moreover, they found that individuals with religious identities are more willing to engage in public environmental protection behaviors than political participants without religious identities. 25 Low-carbon behavior derives from corporate social responsibility. 26 Employee low-carbon behavior is an environmental behavior in employees' daily life.…”
Section: Literature Review and Hypothesis Development Taoism And Empl...mentioning
confidence: 99%